Insights into the metabolic response to traumatic brain injury as revealed by 13C NMR spectroscopy - Bartnik-Olson, Brenda; Harris, Neil; Shijo, Katsunori; Sutton, Richard (Frontiers in Neuroenergetics, 2013)
The present review highlights critical issues related to cerebral metabolism following traumatic brain injury (TBI) and the use of 13C labeled substrates and nuclear magnetic resonance (NMR) spectroscopy to study these changes. First we address some pathophysiologic factors contributing to metabolic dysfunction following TBI. We then examine how 13C NMR spectroscopy strategies have been used to investigate energy metabolism, neurotransmission, the intracellular redox state, and neuroglial compartmentation following injury. 13C NMR spectroscopy studies of brain extracts from animal models of TBI have revealed enhanced glycolytic production of lactate, evidence of pentose phosphate pathway (PPP) activation, and alterations in neuronal and astrocyte oxidative metabolism that are dependent on injury severity. Differential incorporation of label into glutamate and glutamine from 13C labeled glucose or acetate also suggest TBI-induced adaptations to the glutamate-glutamine cycle.